PENERAPAN TEKNOLOGI PEMBENIHAN IKAN GABUS HARUAN SECARA SEMI BUATAN UNTUK KELOMPOK PEMBUDIDAYA IKAN “MUFAKAT” DESA MAHANG BARU, KALIMANTAN SELATAN - Pahmi Ansyari; Slamat Slamat (Jurnal Ilmiah Hospitality, 2022)
Snakehead fish is an important economic fish with increasing economic value because of its distinctive and delicious taste and high protein and albumin content. The development of snakehead fish farming does not develop rapidly, where one of the contributing factors is the continuous availability of seeds. This community service activity was carried out from September to December 2019 with the target audience of the “Mufakat” Fish Cultivator Group, Mahang Baru Village, South Labuan Amas District, Hulu Sungai Tengah Regency, South Kalimantan Province. The implementation method is through lectures, FGDs, short training, demonstrations, and mentoring. The facilities for hatchery of snakehead fish are in the form of 6 (six) tarpaulin ponds measuring 2.5 m x 1.5 m x 1 m. The results of hatchery activities obtained an average egg hatchability of 84.1% and the survival rate from larvae to 2-month-old seed reached 43.81%. Profits obtained during one production cycle (3 months) reached IDR 10,237,500, -, B/C ratio = 1.83 and return on capital = 1.22 period. The results of the average similarity test to the target audience were found to be successful in increasing knowledge and skills of snakehead fish hatchery after the activity.